2007
DOI: 10.3892/ijo.31.4.721
|View full text |Cite
|
Sign up to set email alerts
|

Expression and roles of keratinocyte growth factor and its receptor in esophageal cancer cells

Abstract: Abstract. The keratinocyte growth factor receptor (KGFR), also known as FGFR2 IIIb, is mainly localized in epithelial cells and is activated by the keratinocyte growth factor (KGF) that is predominantly synthesized by mesenchymal cells. In this study, we examined the roles of KGFR and KGF in human esophageal cancer (EC). In noncancerous esophageal tissues, KGFR was localized in epithelial cells from the basal region of the epithelium to the lower one-third of the epithelium, and KGF was weakly localized in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 21 publications
(34 reference statements)
1
26
0
Order By: Relevance
“…There were 11 predicted targets for mir423 . Two of them, PABPC1 (41) and FGFR2 (42), were shown to be associated with the etiology or prognosis of esophageal cancer. Takashima et al (41) demonstrated that down-regulation of PABPC1 was associated with tumor progression, including increased tumor size, locally invasive tumors, and poor overall survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 11 predicted targets for mir423 . Two of them, PABPC1 (41) and FGFR2 (42), were shown to be associated with the etiology or prognosis of esophageal cancer. Takashima et al (41) demonstrated that down-regulation of PABPC1 was associated with tumor progression, including increased tumor size, locally invasive tumors, and poor overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Takashima et al (41) demonstrated that down-regulation of PABPC1 was associated with tumor progression, including increased tumor size, locally invasive tumors, and poor overall survival. Yoshino et al (42) showed that over-expression of FGFR2 was highly correlated with well-differentiated esophageal cancer. Six HOX genes including HOXA5 , HOXA7 , HOXA9 , HOXB6 , HOXB7 , and HOXC8 , were among the predicted targets of mir196a-2 .…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant human KGF could enhance several parameters of cellular motility in estrogen receptor (ER)-positive breast cancer cell lines but not in ER-negative cell lines [39]. Yoshino et al investigated the role of KGFR and KGF in human esophageal cancer (EC) [40]. In EC tissues, KGFR and KGF were expressed in cancer cells in 22 and 37 of 54 patients, respectively.…”
Section: The Function Of Kgf and Kgfr In Solid Cancermentioning
confidence: 99%
“…Overexpression of KGFR can lead to mitogenesis and tumor progression in some cancer types [37][38][39][40][41].…”
Section: The Function Of Kgf and Kgfr In Solid Cancermentioning
confidence: 99%
“…3 In addition, over-expression of KGF and/or KGFR is associated with the progression of several types of cancers including colorectal cancers. 4–7 KGF/KGFR signaling via the ERK1/2 pathway often occurs early in the process of cancer cell initiation by enhancing cell proliferation and motility resulting in progression to a metastatic phenotype. 8 Colorectal cancers are thought to arise due to a series of histopathologic and molecular changes that transform normal colonic epithelial cells into colorectal carcinoma, with an adenomatous polyp as an intermediate step in this process.…”
mentioning
confidence: 99%